Association of Metastatic Colorectal Cancer and its Treatment - Muhammad Naeem, Irfan Ullah, Faiz Shakeel, Fayaz Ahmed Memon, Furqan Tahir, Zaid Gul, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to diagnose metastatic colorectal cancer and its treatment. Study Design: Retrospective/observational study Place and Duration: Department of Gastroenterology, HITEC-IMS Taxila Cantt. 1st July, 2021 To 31 December, 2021 Methods: There 150 patients of both genders were presented in this study. Included patients were aged between 25-85 years. All the presented patients had confirmed metastatic colorectal cancer diagnosed by using CT scan. Informed permission was obtained prior to obtaining detailed demographics, including age, sex and BMI, for all enrolled patients. Mutation of metastatic CRC were recorded and treated in terms of three line treatments by combination of biological and chemotherapy. SPSS 22.0 was used to analyze all data. Results: Males were higher in numbers 90 (60%) than females 60 (40%). Mean age of the patients was 62.16±22.56 years and had mean BMI 9.12 ± 11.45 kg/m2. Most common symptoms were pain in bones, constipation, diarrhea, rectal bleeding and difficulty in breathing among all cases. Frequency of RAS mutation was found in 100 (66.7%) cases, BRAF mutation in 20 (13.3%) cases and MSI-H/dMMR was found in 12 (8%) cases. According to mutational status as first line therpay, frequency of biological targeted therapies in combination with fluoropyrimidine/based combination chemotherapy was 105 (70%), and frequency of combination chemotherapy alone was among 45 (30%) cases. We found 80 (53.3%) patients received biological targeted therapies in combination with chemotherapy, frequency of immunotherapy was 35 (23.3%), combination chemotherapy in 20 (13.3%) and biological targeted therapies in 15 (10%) cases at second line while at third line, combination chemotherapy was received in 90 (60%) cases, frequency of biological targeted therapies was 40 (26.7%), biological targeted therapies in combination with chemotherapy in 13 (8.7%) cases and immunotherapy in 7 (4.7%) cases. Conclusion: This research found that mCRC is a social problem for healthcare systems since therapy is longer but increases patient survival. RAS mutations were frequent. Advances in molecular profiling of metastatic CRC help tailor therapy to particular patient subgroups. Despite few treatments, patients might expect longer longevity. Genomic profiling helps choose treatments so more patients benefit and fewer are exposed to harm.